Role of endogenous incretins in the regulation of postprandial lipoprotein metabolism. Issue 1 (19th May 2022) - Taskinen, Marja-Riitta; Matikainen, Niina; Björnson, Elias; Söderlund, Sanni; Ainola, Mari; Hakkarainen, Antti; Lundbom, Nina; Sihlbom, Carina; Thorsell, Annika; Andersson, Linda; Adiels, Martin; Hartmann, Bolette; et al.
Abstract: Objective: Incretins are known to influence lipid metabolism in the intestine when administered as pharmacologic agents. The aggregate influence of endogenous incretins on chylomicron production and clearance is less clear, particularly in light of opposing effects of co-secreted hormones. Here, we tested the hypothesis that physiological levels of incretins may impact on production or clearances rates of chylomicrons and VLDL. Design and methods: A group of 22 overweight/obese men was studied to determine associations between plasma levels of glucagon-like peptides 1 and 2 (GLP-1 and GLP-2) and glucose-dependent insulinotropic polypeptide (GIP) after a fat-rich meal and the production and clearance rates of apoB48- and apoB100-containing triglyceride-rich lipoproteins. Subjects were stratified by above- and below-median incretin response (area under the curve). Results: Stratification yielded subgroups that differed about two-fold in incretin response. There were neither differences in apoB48 production rates in chylomicrons or VLDL fractions nor in apoB100 or triglyceride kinetics in VLDL between men with above- vs below-median incretin responses. The men with above-median GLP-1 and GLP-2 responses exhibited higher postprandial plasma and chylomicron triglyceride levels, but this could not be related to altered kinetic parameters. No differences were found between incretin response subgroups and particle clearance rates. Conclusion: We found no evidence for a regulatory effect of endogenous incretins on contemporaneous chylomicron or VLDL metabolism following a standardised fat-rich meal. The actions of incretins at pharmacological doses may not be reflected at physiological levels of these hormones.